The Inexhaustible - Voet, Rosanne van der (Journal of Posthumanism, 2023)
Adopting a hybrid, creative-critical approach, this article explores how Rosi Braidotti’s notion of posthuman subjectivity based on a negotiation between humans, zoe (nonhumans), geo (earth) and techno (technologies) can be put into practice creatively. Against the background of the low-lying South Holland coast, where sandscapes based on human-nonhuman collaborations prevent coastal erosion, I trace the various voices in the landscape complementing and interrupting each other. Shifting from a human perspective into the perspectives of zoe, geo and techno, the narration of this piece finally coalesces to form a new ‘we’ which represents this posthuman subjectivity. Imagining alternate futures based on this inclusive ‘we,’ this piece explores what a collaboration based on a collective posthuman subjectivity can mean in practice. Moreover, it demonstrates the potential of experiments in form and style to make tangible theoretical insights from posthuman scholarship, introducing an innovative approach that bridges the gap between academic and creative writing.